Sentidos e efeitos da avaliação externa do Programa Alfabetização na Idade Certa (PAIC) na Rede Municipal de Ensino Público de Fortaleza (CE) - Silveira, Teresa Márcia Almeida da (2015)
The objective of this research is to evaluate the external evaluation of the shaft Literacy Program in the Middle One (PAIC), public education policy of the Government of the State of Ceará, which aims literate children from public school until the age of seven. This evaluative research breaks with the design of managerial evaluation, based on the measurement and value judgment and relies on the concept of evaluation of public policies embedded in a comprehensive and thoughtful approach. From this perspective, it assumes an in-depth evaluation in the design of Rodrigues (2008), from the post-constructivist approach of Lejano (2012), in which the evaluation means going beyond PAIC text analysis and part to Search understanding of the context fields and experiences of educational actors. Is adopted as the object evaluation the axis of the external evaluation of PAIC, trying to understand how educational actors in the municipal public education Fortaleza realize and conduct the external evaluation of PAIC and explaining the effects of the outcome of the trial PAIC. It uses a methodological-theoretical path centered on a ethnographic essay, based on Malinowski (1975) and Laplantine (2004), with qualitative approach procedure, which allows entering the PAIC the process to understand the meaning, the senses and the effects of axis of the external evaluation of PAIC. The theoretical foundation is guided in the conceptions of educational assessment formative, advocated by Afonso (2005), Hadji (2001) and Perrenoud (1999), as well as in studies of school culture Forquin (1993) and Julia (2001). Through immersion in the field of the PAIC practice, the search key is found by empirical analysis categories - background and text -, revealing the context dimensions is conceptual, and symbolic instrument. The dimensions indicate evidence beyond the text of the external evaluation of PAIC, if noting that the PAIC Proof is not shaped in a formative and diagnostic assessment. It is evident that the external evaluation of PAIC causes an educational centering around the Reference Array descriptors, setting the school curriculum. One sees an imposition of "evaluative culture" prompted by managing for results, in which the results of the trial PAIC fall in accountability, resulting in rankings of public schools in Fortaleza.